Synthesis of Nanocrystalline MgO Particles by Combustion Followed by Annealing Method Using Hexamine as a Fuel - S. Balamurugan; L. Ashna; P. Parthiban (Journal of Nanotechnology)
In this work, nanocrystalline MgO particles were prepared through combustion method using magnesium nitrate as oxidizer and hexamine as a fuel. The materials obtained by combustion method were subsequently annealed at 800°C for 3 h to improve the crystallinity and phase purity. The obtained MgO nanomaterials were characterized by powder X-ray diffraction analysis (XRD), infrared (IR) spectroscopy, photoluminescence (PL), near-infrared (NIR) spectroscopy, and scanning electron microscopy (SEM). The cubic crystal structure with lattice parameter, a = 0.4210(4) nm with average crystalline size of 22 nm, is obtained for the nano-MgO particles. The PL emission spectrum of nanocrystalline MgO materials exhibits three emission peaks at 432, 465, and 495 nm which are due to various structural defects. The SEM results expose the fact that the MgO nanomaterials are seemingly porous and highly agglomerated with fine particles. Owing to the higher reflectance of prepared nanocrystalline MgO, it can be used as NIR reflective pigments. The present results prove that the combustion technique using hexamine can produce the materials with high crystallinity. To the best of our knowledge, this is the first report on the synthesis of nanocrystalline MgO materials by combustion method using hexamine as a fuel.